Differences in induction phase outcomes of acute lymphoblastic leukemia between well-nourished and malnourished pediatric patients - Meilani Puspasari Simarmata; Nelly Rosdiana; Arlinda Sari Wahyuni (Paediatrica Indonesiana, 2023)
Background Leukemia is the most common malignancy in childhood. Malnutrition is the main nutritional disorder occurring in children with cancer. Nutritional supportive care is a medical modality that has been associated with improved tolerance to chemotherapy, survival, and quality of life, as well as decreased risk of infection in children undergoing cancer therapy. Objective To examine differences in induction phase outcomes in well-nourished and malnourished pediatric acute lymphoblastic leukemia (ALL) patients. Methods This prospective study was conducted in newly-diagnosed ALL patients aged 1 to 18 years who underwent induction phase chemotherapy at Haji Adam Malik General Hospital, Medan, North Sumatera. Mid-upper arm circumference (MUAC) was used to determine nutritional status. Patient characteristics such as complete blood count (CBC) at the time of diagnosis, occurrence of febrile neutropenia, duration of induction, length of hospital stay, and remission status were collected. We analyzed differences in CBC, frequency of febrile neutropenia, as well as duration of induction and hospital stay between well-nourished and malnourished patients. We also assessed the difference in remission attainment between the two groups. Results There were 21 subjects in each group. Compared to well-nourished subjects, malnourished ones had a higher median incidence of febrile neutropenia [1 (range 0 to 30) vs. 3 (range 0 to 4); P=0.04], longer mean induction duration [64.2 (SD 11.5) vs. 71.2 (SD 10.6) days; P=0.046], and longer median hospital stay [30 (range 19 to 56) vs. 36 (range 22 to 49) days; P=0.001] compared to well-nourished subjects. There was no significant difference in CBC parameters and remission status after induction between the two groups. Conclusion Malnourished pediatric ALL patients had a significantly higher incidence of febrile neutropenia, duration of induction phase, and duration of hospital stay compared to well-nourished ALL patients.